Evaluation of a plastic clay from the state of Rio de Janeiro as a component of porcelain tile body - Vieira,C. M. F. (2007)
The objective of this work was to evaluate the possibility of using a clay from the city of Silva Jardim, State of Rio de Janeiro, Brazil, in the composition of porcelain tile body. The clay investigated was a plastic kaolinitic type with white color. Initially, a typical porcelain body composed of the mixture of this clay with feldspar, quartz, kaolin and talc was prepared. Specimens were then obtained from this porcelain mixture by uniaxially pressing samples until a dry density of 2.0 g/cm3 was achieved. These specimens were then fired at 1180°C in a laboratory furnace. Physical and mechanical properties related to linear shrinkage, water absorption and flexural rupture strength, determined by Weibull statistical method, were evaluated. Microstructural analysis for the experimental body was performed by scanning electron microscopy, X-ray diffraction and mercury porosimetry. The technological properties of the elaborated composition satisfied the porcelain tile standard specifications. The microstructural analysis displayed small pores as well as a glassy matrix. The presence of quartz, mullite and plagioclase were also detected in the fired porcelain tile. These results indicated that the clay presents satisfactory characteristics to be used in porcelain tile body.